Does breast MRI background parenchymal enhancement indicate metabolic activity? Qualitative and 3D quantitative computer imaging analysis. Issue 3 (24th June 2017) - Mema, Eralda; Mango, Victoria L.; Guo, Xiaotao; Karcich, Jenika; Yeh, Randy; Wynn, Ralph T.; Zhao, Binsheng; Ha, Richard S.
Abstract : Purpose: To investigate whether the degree of breast magnetic resonance imaging (MRI) background parenchymal enhancement (BPE) is associated with the amount of breast metabolic activity measured by breast parenchymal uptake (BPU) of 18F‐FDG on positron emission tomography / computed tomography (PET/CT). Materials and Methods: An Institutional Review Board (IRB)‐approved retrospective study was performed. Of 327 patients who underwent preoperative breast MRI from 1/1/12 to 12/31/15, 73 patients had 18F‐FDG PET/CT evaluation performed within 1 week of breast MRI and no suspicious findings in the contralateral breast. MRI was performed on a 1.5T or 3.0T system. The imaging sequence included a triplane localizing sequence followed by sagittal fat‐suppressed T2 ‐weighted sequence, and a bilateral sagittal T1 ‐weighted fat‐suppressed fast spoiled gradient‐echo sequence, which was performed before and three times after a rapid bolus injection (gadobenate dimeglumine, Multihance; Bracco Imaging; 0.1 mmol/kg) delivered through an IV catheter. The unaffected contralateral breast in these 73 patients underwent BPE and BPU assessments. For PET/CT BPU calculation, a 3D region of interest (ROI) was drawn around the glandular breast tissue and the maximum standardized uptake value (SUVmax ) was determined. Qualitative MRI BPE assessments were performed on a 4‐point scale, in accordance with BI‐RADS categories. Additional 3D quantitative MRI BPE analysis was performed using a previously published in‐house technique. Spearman's correlation test and linear regression analysis was performed (SPSS, v. 24). Result: The median time interval between breast MRI and 18F‐FDG PET/CT evaluation was 3 days (range, 0–6 days). BPU SUVmax mean value was 1.6 (SD, 0.53). Minimum and maximum BPU SUVmax values were 0.71 and 4.0. The BPU SUVmax values significantly correlated with both the qualitative and quantitative measurements of BPE, respectively ( r (71) = 0.59, P < 0.001 and r (71) = 0.54, P < 0.001). Qualitatively assessed high BPE group (BI‐RADS 3/4) had significantly higher BPU SUVmax of 1.9 (SD = 0.44) compared to low BPE group (BI‐RADS 1/2) with an average BPU SUVmax of 1.17 (SD = 0.32) ( P < 0.001). On linear regression analysis, BPU SUVmax significantly predicted qualitative and quantitative measurements of BPE (β = 1.29, t (71) = 3.88, P < 0.001 and β = 19.52, t (71) = 3.88, P < 0.001). Conclusion: There is a significant association between breast BPU and BPE, measured both qualitatively and quantitatively. Increased breast cancer risk in patients with high MRI BPE could be due to elevated basal metabolic activity of the normal breast tissue, which may provide a susceptible environment for tumor growth. Level of Evidence : 3 Technical Efficacy : Stage 3 J. Magn. Reson. Imaging 2018;47:753–759.